CRECIMIENTO DE Zea mays L. var. Canteño INOCULADO CON Glomus intraradices SCHENK & SMITH Y SOMETIDO A ESTRÉS SALINO - Ruiz Flores, Walter (2016)
Zea mays L. var. Canteño, is used as a natural pigment in the food and beverage industry; as well as being the second maize variety on Peru's export list; so its cultivation is being promoted in several regions of the country. The arbuscular mycorrhizal fungus (HMA) Glomus intraradices is used in agriculture as an efficient alternative to improve the growth of plants, as well as to increase their tolerance to abiotic stress conditions, such as salinity. In this work, it was proposed to evaluate the growth of Zea mays L. var. Canteño inoculated with Glomus intraradices Schenk & Smith and subjected to saline stress; For which plants of 15 days of age were inoculated with Glomus and subjected to concentrations of 0, 25, 50 and 100 mM of NaCl for 45 days. The length of the aerial part of the plant and of the leaf blade was measured; As well as the number of leaves. It was found that in plants treated with uninoculated NaCl and inoculated with Glomus, the length of the aerial part of the plant significantly decreased compared to the control plants, the lowest values were recorded in plants treated with 100 mM NaCl. In the inoculated and treated plants with 25, 50 and 100 mM NaCl, the values of this parameter were significantly higher than in the non-inoculated plants. For leaf length and leaf number, significant differences were also found in both non-inoculated and Glomus inoculated and NaCl treated plants. The inoculation with Glomus intraradices schenk & Smith, promoted a greater growth of the aerial part of Zea mays L. var, Canteño treated with 0, 25, 50 and 100 mM of NaCl, than in the uninoculated plants.